Effect of the Timing of Anterior Cruciate Ligament Reconstruction on Clinical and Stability Outcomes: A Systematic Review and Meta-analysis - Lee, Yong Seuk; Lee, O-Sung; Lee, Seung Hoon; Teo, Seow Hui (Elsevier, 2018)
Purpose: The purpose of this systematic review and meta-analysis was to evaluate the effect of the timing of anterior cruciate ligament (ACL) reconstruction on clinical and stability outcomes by analyzing high-quality studies that assessed timing as a primary objective. Methods: The MEDLINE, EMBASE, and Cochrane database were systematically searched. The inclusion criteria were as follows: (1) English articles, (2) noncomparative study or relevant study reporting clinical and/or stability results, and (3) timing of the ACL reconstruction as a primary objective. Study type, level of evidence, randomization method, exclusion criteria, number of cases, age, sex, timing of ACL reconstruction, follow-up, clinical outcomes, stability outcomes, and other relevant findings were recorded. Statistical analysis of the Lysholm scores and KT-1000 arthrometer measurements after early and delayed ACL reconstruction was performed using R version 3.3.1. Results: Seven articles were included in the final analysis. There were 6 randomized controlled trials and 1 Level II study. Pooled analysis was performed using only Level I studies. All studies assessed the timing of ACL reconstruction as a primary objective. The definition of early ranged broadly from 9 days to 5 months and delayed ranged from 10 weeks to >24 months, and there was an overlap of the time intervals between some studies. The standard timing of the delayed reconstruction was around 10 weeks from injury in the pooled analysis. After pooling of data, clinical result was not statistically different between groups (I2: 47%, moderate level of heterogeneity). No statistically significant difference was observed in the KT-1000 arthrometer measurements between groups (I2: 76.2%, high level of heterogeneity) either. Conclusion: This systematic review and meta-analysis performed using currently available high-quality literature provides relatively strong evidence that early ACL reconstruction results in good clinical and stability outcomes. Early ACL reconstruction results in comparable clinical and stability outcomes compared with delayed ACL reconstruction. Level of Evidence: Level II, a systematic review and meta-analysis of Level I and II studies.